An analysis of the impact of IT software architecture on business transformation strategy. - Jackson, Sharon (My University, 1997)
Managers are increasingly aware that they need to leverage their company's resources in order to deal with the challenges of the changing business world in the 90' s and the coming millennium. The aim of this research is to evaluate how organisations are utilising enterprise wide packaged software applications in order to achieve strategic and transformational benefits for their organisations. The relentless change in the business landscape has meant that organisations have needed to respond in increasingly innovative ways to stay in business. This has been more so for South African organisations which have now been accepted back into the world community after years of isolation due the country's political policy of apartheid. The watershed years of the early 1990's opened up once forbidden markets to South African organisations and in doing so launched these organisations into a global competitive environment. To compete effectively in these newly opened and changed markets, companies have sought to reposition themselves. Since information technology is clearly embedded in many of these organisations they are increasingly turning to infonnetion technology to underpin their new businesses strategies. The relevance of the information architecture an organisation chooses will also be explored in this research, as the flexibility and structure of the architecture will determine what strategic options are available to the company. Many organisations are implementing software packages as opposed to writing their own software to fit unique processes. This trend is strengthened by advancements on the technological front, the disappointment of cost overruns with previously in-house written applications, and the critical shortage of experienced IT (information technology) skills ill the country. Business can no longer wait years for a system to be developed. The implementation of enterprise wide packaged software applications facilitates integration and process transformation which many organisations see as fundamental to their new strategies to remain competitive. This research showed that the implementation of enterprise wide packaged software applications forces change on an organisation in that a number of domains within the organisation are challenged. Processes need revisiting, human resources undergo a change and teamwork is facilitated. There is a new sharing of knowledge and information within the organisation, and such information systems are deployed rapidly and with the business objectives firmly in place. Whilst there were strategic and transformational benefits, there were also a number of unexpected benefits. The changes brought about by such implementations were largely underestimated by managers within these organisations.
This thesis is submitted in partial fulfilment of the requirements of the degree of Master of Commerce in the University of the Witwatersrand, Johannesburg.
Keywords: Organizational change.; Computer software.; Management information systems.